Wali Kelas sebagai Ibu Kedua: Strategi, Kendala, dan Kunci Motivasi Santriwati TMI Putri Al-Amien Prenduan - Afifah Afifah; Vivi Rohmatun Nadia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the perspective of TMI Putri Al-Amien Prenduan in increasing the learning motivation of intensive class I students and identify the obstacles and supporting elements. The approach used is qualitative with the type of case study. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through condensation, presentation, and conclusion drawing with source triangulation for data validation. The results of the study show that the homeroom teacher of TMI Putri Al-Amien Prenduan perspective has three special tasks, namely in the educational, functional, and structural fields. Furthermore, the role of homeroom teachers in increasing the learning motivation of intensive class I students at TMI Putri Institution includes: homeroom teachers as educators, motivators, good role models, substitutes for parents at home, companions, facilitators, building positive relationships, and providing rewards and punishments. And the obstacles faced by homeroom teachers in increasing the learning motivation of Intensive I students include: inability to participate in learning and cottage activities, the nature of students is less open, and students are difficult to regulate. Meanwhile, the supporting elements of homeroom teachers in increasing learning motivation I Intensive are: The existence of facilities, homeroom training, homeroom teacher seriousness, support for homeroom teachers and involving the role of parents.